Production of Labile Protein-Like Dissolved Organic Carbon Associated With Anaerobic Methane Oxidization in the Haima Cold Seeps, South China Sea - Hu, Tingcang; Luo, Min; Xu, Yunping; Gong, Shanggui; Chen, Duofu (Frontiers in Marine Science, 2021)
Cold seeps where methane-rich fluids escape from the seafloor generally support enormous biomass of chemosynthetic organisms and associated fauna. In addition to transporting a great amount of methane toward the seafloor, cold seeps also contribute to the aged, dissolved organic carbon (DOC) pool in the deep ocean. Here, two sediment cores from the “Haima cold seeps,” northern South China Sea and a nearby reference core were analyzed for pore-water sulfate and DOC concentrations, δ13C of DOC, and optical properties of dissolved organic matter (DOM). High DOC concentrations (0.9–3.7 mM) accompanied by extremely low δ13C values (−43.9 to −76.2‰) suggest the conversion of methane into sedimentary DOC pool in the seep sediments. Parallel factor analysis (PARAFAC) of the fluorescence excitation-emission matrices shows higher fluorescent intensities of labile protein-like components (C2 and C4) and lower fluorescent intensities of refractory humic-like components (C1 and C3) in the seep cores compared to the reference core. The intensity of C2 is positively correlated with DOC concentrations and δ13C-DOC in the seep sediments, suggesting that the labile protein-like DOM was produced by the anaerobic oxidation of methane (AOM). Moreover, low humification index (HIX) and high biological index (BIX) values also indicate intensified production of relatively labile DOM with lower degradation degree in the seep cores compared to the reference core. Hence, we highlight that methane-derived DOC may serve as important carbon and energy sources for heterotrophic microbial communities due to its relatively labile nature.